Differential NO3 - dependent patterns of NO3 - uptake in Pinus pinaster, Rhizopogon roseolus and their ectomycorrhizal association - Gobert, Anthony (The New phytologist, 2002)
•  A different NO3 - dependent pattern of NO3 - uptake at low [NO3 - ] (0-0.1 mM) is shown in Pinus pinaster and in the ectomycorrhizal fungus Rhizopogon roseolus. In ectomycorrhizal symbiosis, the fungal pattern is pre-eminent. •  Net NO3 - uptake rates were deduced in plant and fungus from solution depletion measurements. Net NO3 - fluxes were estimated at the surface of mycorrhizal and nonmycorrhizal short roots, using NO3 - selective microelectrodes. •  In NO3 - starved seedlings, maximum NO3 - uptake rates were reached after 3 d of incubation in 0.05 mM NO3 - . In R. roseolus mycelia, NO3 - uptake rates did not change after withdrawing NO3 - for up to 7 d, or after adding NO3 - for 3 d. Net NO3 - fluxes in nonmycorrhizal short roots were increased twofold by a 3-d exposure to NO3 - whereas in ectomycorrhiza they were similar irrespective of the NO3 - pretreatment, but always higher than the fluxes measured in nonmycorrhizal roots. •  Ectomycorrhiza have a greater capacity to use NO3 - than nonmycorrhizal short roots, whatever the NO3 - concentration in the solution. This may give mycorrhizal plants a greater ability to use fluctuating concentrations of NO3 - in the soil solution